2014
DOI: 10.1103/physreve.89.052401
|View full text |Cite
|
Sign up to set email alerts
|

History-dependent friction and slow slip from time-dependent microscopic junction laws studied in a statistical framework

Abstract: To study how macroscopic friction phenomena originate from microscopic junction laws, we introduce a general statistical framework describing the collective behavior of a large number of individual micro-junctions forming a macroscopic frictional interface. Each micro-junction can switch in time between two states: A pinned state characterized by a displacement-dependent force, and a slipping state characterized by a time-dependent force. Instead of tracking each micro-junction individually, the state of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 67 publications
4
39
0
Order By: Relevance
“…In the latter case it manifests itself as a result of the microscopic junctions formed due to the sliding of micro-asperities against each other. 39,40 Such situations might arise in partially saturated sediments as well as where the grains could come into direct contact with each other, and still exhibit time-dependent behavior.…”
Section: Grain-shearing Modelmentioning
confidence: 99%
“…In the latter case it manifests itself as a result of the microscopic junctions formed due to the sliding of micro-asperities against each other. 39,40 Such situations might arise in partially saturated sediments as well as where the grains could come into direct contact with each other, and still exhibit time-dependent behavior.…”
Section: Grain-shearing Modelmentioning
confidence: 99%
“…These micro-junctions have an inherent property of being time-dependent. 47 One of the goals achieved through this work is that we have shown that the equations derived from the fundamental physical process of grain-shearing could lead to fractional-order wave equations. This may be the first result which directly connects the fractional framework to a process deeply rooted in physics.…”
Section: Discussionmentioning
confidence: 99%
“…We have assumed that broken contacts are immediately restored with zero stretching. Instead, one may assume that the contacts repin after some delay time τ d [10,14,15,21,9]. Assuming a constant τ d , the width of the self-healing crack will increase from λ c to vτ d , with v the (minimal) propagation velocity of the front (see Refs.…”
Section: Discussionmentioning
confidence: 99%